Rheumatic myocarditis: a poorly recognized etiology of left ventricular dysfunction in valvular heart disease patients. (14th October 2021) - Emer Egypto Rosa, V; Lopes, M P; Spina, G S; Soares Jr, J; Salazar, D; Romero, C E; Lottemberg, M P; De Santis, A; Pires, L J N T; Goncalves, L F T; Fernandes, J R C; Sampaio, R O; et al.
Abstract: Background: Heart failure is present in about 10% of patients with acute rheumatic fever (RF), and several studies showed that cardiac decompensation in RF results primary from valvular disease, and not due to primary myocarditis. However, literature is scarce in this topic and a recent case series showed that recurrent RF could cause ventricular dysfunction even in the absence of valvular heart disease. Purpose: To evaluate clinical, laboratory and echocardiographic profile of rheumatic fever patients with confirmed myocarditis diagnosis using Fluorine-18-fluorodeoxyglucose positron emission tomography (18F-FDG PET/CT) or Gallium-67 cardiac scintigraphy. Methods: Clinical, laboratory and imaging characteristics of 25 consecutive patients with diagnosis of myocarditis, using 18F-FDG PET/CT or gallium-67 cardiac scintigraphy (Figure 1A and 1B, respectively), and RF reactivation according to revised Jones Criteria, were evaluated. Patients underwent 3 sequential echocardiograms: (1) baseline, (2) during myocarditis and (3) post- corticosteroid treatment, and were divided according to the presence (Group 1) or absence (Group 2) of reduced left ventricular ejection fraction (LVEF) during myocarditis episode. Results: Median age was 42 (17–51) years, 64% had more than 40 years and 64% were women. Comparing patients in Group 1 (n=16) with Group 2 (n=9), there was no demographic, echocardiographic or laboratory difference between groups, except for NYHA III/IV heart failure (Group 1: 100.0% versus Group 2: 50.0%; p=0.012) and LVEF (30 [25–37] versus 56 [49–62] %, respectively; p<0.001), as expected. Group 1 patients had significant reduction of LVEF during carditis with further improvement after treatment (Figure 1C). There was no correlation between LVEF and valvular dysfunction during myocarditis. Of all patients, 19 (76%) underwent 18F-FDG PET/CT, with positive scan in 68.4% and 21 (84%) underwent Gallium-67 cardiac scintigraphy, with positive uptake in 95.2%, both with no difference between groups. Conclusion: Myocarditis due to rheumatic fever reactivation can cause left ventricular dysfunction despite of valvular disease, and is reversible after corticosteroid treatment. Funding Acknowledgement: Type of funding sources: None.